Factors Related to the Nurse's Motivation on Fulfilling the Personal Hygiene of Patients in Total Care - Wahyudi, Andri Setiya; Pradanie, Retnayu; Klau, Oktovianus Tahu (International Journal of Psychosocial Rehabilitation, 2020)
The personal hygiene of a patient is maintained by their nurse. The implementation of personal hygiene depends on the motivation of the nurse. Low nurse motivation in relation to personal hygiene af ects the patient’s recovery. The purpose of this research was to determine the factors related to the nurse's motivation to fulfill the personal hygiene of the patients under total care. A cross-sectional design was conducted in this study in addition to the observation of the population which consisted of 9 Executer nurses taking care of lodged adults in the Regions Common Hospital Prof. Dr. W. Z. Yohanesz Kupang. The sample consisted of 106 respondents that met the inclusion criterion. The dependent variable was motivation. The independent variables were responsibility, pay, working condition, working safety and the co-worker/superior relationship. The data collected utilized a questionnaire that had already been modified and tested. The analysis used logistic regression. There was a relationship between two of the factors and logistic regression, namely the factor of responsibility (p = 0.0000) and the working relationship (p = 0.025). Some of the factors that were rejected were reward (p = 0.275), working conditions (p = 0.951) and work safety (p = 0.999). The nurse’s motivation is related to the factors of responsibility and their work relations. It was expected that this research can have a positive impact on the nurses, especially in reference to the personal hygiene of the total care patients, by providing broader opportunities for the nurses to better the personal hygiene of the patients under their total care.